Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Para resolver el problema, vamos a utilizar la relación dada [tex]\( a_{n+1} = 3 a_n - 2 a_{n-1} \)[/tex] y los valores iniciales [tex]\( a_1 = 2 \)[/tex] y [tex]\( a_2 = 3 \)[/tex]. Queremos encontrar el valor de [tex]\( a_4 + a_6 \)[/tex].
Primero, calculemos [tex]\( a_3 \)[/tex]:
[tex]\[ a_3 = 3a_2 - 2a_1 \][/tex]
Sustituyendo [tex]\( a_2 = 3 \)[/tex] y [tex]\( a_1 = 2 \)[/tex]:
[tex]\[ a_3 = 3(3) - 2(2) \][/tex]
[tex]\[ a_3 = 9 - 4 \][/tex]
[tex]\[ a_3 = 5 \][/tex]
Ahora calculemos [tex]\( a_4 \)[/tex]:
[tex]\[ a_4 = 3a_3 - 2a_2 \][/tex]
Sustituyendo [tex]\( a_3 = 5 \)[/tex] y [tex]\( a_2 = 3 \)[/tex]:
[tex]\[ a_4 = 3(5) - 2(3) \][/tex]
[tex]\[ a_4 = 15 - 6 \][/tex]
[tex]\[ a_4 = 9 \][/tex]
A continuación, calculamos [tex]\( a_5 \)[/tex]:
[tex]\[ a_5 = 3a_4 - 2a_3 \][/tex]
Sustituyendo [tex]\( a_4 = 9 \)[/tex] y [tex]\( a_3 = 5 \)[/tex]:
[tex]\[ a_5 = 3(9) - 2(5) \][/tex]
[tex]\[ a_5 = 27 - 10 \][/tex]
[tex]\[ a_5 = 17 \][/tex]
Finalmente, calculemos [tex]\( a_6 \)[/tex]:
[tex]\[ a_6 = 3a_5 - 2a_4 \][/tex]
Sustituyendo [tex]\( a_5 = 17 \)[/tex] y [tex]\( a_4 = 9 \)[/tex]:
[tex]\[ a_6 = 3(17) - 2(9) \][/tex]
[tex]\[ a_6 = 51 - 18 \][/tex]
[tex]\[ a_6 = 33 \][/tex]
Ahora sumamos [tex]\( a_4 \)[/tex] y [tex]\( a_6 \)[/tex]:
[tex]\[ a_4 + a_6 = 9 + 33 \][/tex]
[tex]\[ a_4 + a_6 = 42 \][/tex]
Por lo tanto, el valor de [tex]\( a_4 + a_6 \)[/tex] es [tex]\(\boxed{42}\)[/tex].
Primero, calculemos [tex]\( a_3 \)[/tex]:
[tex]\[ a_3 = 3a_2 - 2a_1 \][/tex]
Sustituyendo [tex]\( a_2 = 3 \)[/tex] y [tex]\( a_1 = 2 \)[/tex]:
[tex]\[ a_3 = 3(3) - 2(2) \][/tex]
[tex]\[ a_3 = 9 - 4 \][/tex]
[tex]\[ a_3 = 5 \][/tex]
Ahora calculemos [tex]\( a_4 \)[/tex]:
[tex]\[ a_4 = 3a_3 - 2a_2 \][/tex]
Sustituyendo [tex]\( a_3 = 5 \)[/tex] y [tex]\( a_2 = 3 \)[/tex]:
[tex]\[ a_4 = 3(5) - 2(3) \][/tex]
[tex]\[ a_4 = 15 - 6 \][/tex]
[tex]\[ a_4 = 9 \][/tex]
A continuación, calculamos [tex]\( a_5 \)[/tex]:
[tex]\[ a_5 = 3a_4 - 2a_3 \][/tex]
Sustituyendo [tex]\( a_4 = 9 \)[/tex] y [tex]\( a_3 = 5 \)[/tex]:
[tex]\[ a_5 = 3(9) - 2(5) \][/tex]
[tex]\[ a_5 = 27 - 10 \][/tex]
[tex]\[ a_5 = 17 \][/tex]
Finalmente, calculemos [tex]\( a_6 \)[/tex]:
[tex]\[ a_6 = 3a_5 - 2a_4 \][/tex]
Sustituyendo [tex]\( a_5 = 17 \)[/tex] y [tex]\( a_4 = 9 \)[/tex]:
[tex]\[ a_6 = 3(17) - 2(9) \][/tex]
[tex]\[ a_6 = 51 - 18 \][/tex]
[tex]\[ a_6 = 33 \][/tex]
Ahora sumamos [tex]\( a_4 \)[/tex] y [tex]\( a_6 \)[/tex]:
[tex]\[ a_4 + a_6 = 9 + 33 \][/tex]
[tex]\[ a_4 + a_6 = 42 \][/tex]
Por lo tanto, el valor de [tex]\( a_4 + a_6 \)[/tex] es [tex]\(\boxed{42}\)[/tex].
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.